College and the grieving student: A mixed-methods analysis. Issue 8 (13th September 2016) - Cupit, Illene Noppe; Servaty-Seib, Heather L.; Tedrick Parikh, Sara; Walker, Andrea C.; Martin, Ryan
ABSTRACT: The current mixed-methods study examines how college students negotiate the grief process with the competing demands of college. Data were collected from 950 students at a regional comprehensive university and a research intensive institution. Quantitative findings revealed closeness to the deceased as a key positive predictor of mental health and academic difficulties and positive associations between changes in peer relationships and mental health difficulties. Qualitative findings showed that closeness to the deceased was associated with a greater sense of purpose in the college experience and findings suggested that institutions and their faculty encourage and exhibit more sensitivity about grief issues.